Hyperlipidemia and male infertility. Issue 1 (1st January 2021) - Hamad Zubi, Zainab Bubakr; Hamad Alfarisi, Hamad Abdulsalam
ABSTRACT: Hyperlipidemia is a common disease affecting 25% of adults in developed nations. Approximately 50% of the middle-aged adult population have been reported to have total cholesterol level above the normal range. Worldwide, the incidence of dyslipidaemia is increasing in both low and high income countries. It is a major risk factor for the prevalence and severity of ischemic heart disease. Less recognized but growing in importance are the effects of dyslipidaemia on reproductive functions. A growing evidence has linked dyslipidaemia and abnormal lipid metabolism with alteration of male fertility. The purpose of this review is to summarize the data gathered from both experimental animal models and human studies on the effects of hyperlipidemia on semen parameters, spermatogenesis, male reproductive organs, hormones and fertility.